Myth or Reality? Mobility Trends among Recent Graduates of Different Fields of Study - Fónai, Mihály; Lánczi, Viktória (Central European Journal of Educational Research, 2023)
The paper focuses on the intergenerational mobility processes in Hungarian higher education over the past decade. Its purpose is to explore these processes and to analyse the differences between the fields of study. The second-generation mobility theories, which serve to be the theoretical background of this paper, focus on the differences between income, education, occupational groups and social classes in connection with status attainment and mobility. Among the mobility theories relating to higher education, theories analyzing inequalities are studied, to discover whether they are found in Hungarian higher education („Maximally Maintained Inequality”, MMI and the theory of „Effectively Maintained Inequality”, EMI). The analysis also covers the „dynastic effects” related to mobility, whether they strengthen or weaken intergenerational processes. The database of the analysis is the Graduate Career Tracking System 2010-2021.